Badiuzzaman Said Nursi and KH Ahmad Dahlan Thoughts on Education Reform: A Comparative Study - Muhammad Sophy Abdul Aziz; Hudzaifah Achmad Qotadah; Adang Darmawan Achmad (International Journal of Islamic Khazanah, 2021)
In order to control the movement of globalization throughout this modern era, one of it's key aspects is through deconstruction throughout the education sector. Undoubtedly, high quality education management was produced by integrating disciplines in practice with fundamental Islamic values within the learning process. Besides that, this approach had also been continuously used among reformist leaders to weaken the dangerous Western ideology that influenced significantly the global government system through colonialism mostly by poisoning the generation of youth through sole reference to materialism philosophy and rationalism. Based on that issue, numerous powerful leaders in Indonesia have intervened to rectify the problem among Muslims by reconstruction of the education systems rather than through political as well as other aggressive physical interaction. KH Ahmad Dahlan was the trustworthy figure in endorsing the concept of educational reform through the "Muhammadiyah" mass organization, which was formed in Yogyakarta in 1912. The conducted a study to examine the similarities amongst KH Ahmad Dahlan and Badiuzzaman Said Nursi in applying the Islamic Education Reform System in the region. In this research, the researcher uses full qualitative method and documentation related to the topic of this research, which then will be analyze descriptively.